Rekam Medik Elektronik: Mengurai Pandangan Filosofis, Sosiologis, Dan Yuridis - Septriana Rosady, Dony; Chasnah, Rachmi; Sarip, Hasan (Jurnal MHKI, 2023)
The increase in allegations of malpractice cases in Indonesia today has opened up awareness of the importance of medical records in health services. Along with the development of technology, the implementation of electronic medical records is also developing. Literature study research was conducted to review various literature related to electronic medical records. A normative juridical approach is carried out towards regulations related to electronic medical records. Electronic medical records must be implemented by health care facilities that provide telemedicine services. These health service facilities include independent practices, community health centers, clinics, hospitals, pharmacies, health laboratories, health centers, and other forms of facilities determined by the Minister. Philosophically, sociologically, and juridically, the implementation of electronic medical records in Indonesia can be implemented and has an impact on improving health services.